2020
DOI: 10.1002/cti2.1122
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in type 1 diabetes: mechanisms of action and immunotherapeutic targets

Abstract: Cytokines play crucial roles in orchestrating complex multicellular interactions between pancreatic β cells and immune cells in the development of type 1 diabetes (T1D) and are thus potential immunotherapeutic targets for this disorder. Cytokines that can induce regulatory functions—for example, IL‐10, TGF‐β and IL‐33—are thought to restore immune tolerance and prevent β‐cell damage. By contrast, cytokines such as IL‐6, IL‐17, IL‐21 and TNF, which promote the differentiation and function of diabetogenic immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
94
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 136 publications
(263 reference statements)
1
94
0
1
Order By: Relevance
“…Numerous studies have demonstrated that the development of ketoacidosis and hyper-glycemia precipitate an inflammatory state due to elevations in proinflammatory cytokines as well as oxidative stress [ 8 10 ]. Hyperglycemia induces macrophages to produce interleukin (IL)-1, IL-6, C-reactive peptide, and tumor necrosis factor-alpha, which reduce the body’s responsiveness to insulin [ 8 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that the development of ketoacidosis and hyper-glycemia precipitate an inflammatory state due to elevations in proinflammatory cytokines as well as oxidative stress [ 8 10 ]. Hyperglycemia induces macrophages to produce interleukin (IL)-1, IL-6, C-reactive peptide, and tumor necrosis factor-alpha, which reduce the body’s responsiveness to insulin [ 8 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic β cell damage due to apoptosis plays an important role in both types of DM. In T1DM, β cell destruction occurs following an autoimmune reaction, which triggers activation of inflammatory cells and secretion of cytokines [ 8 ]. This will eventually activate the apoptotic pathways in the pancreatic β cells [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the major signaling pathways that is heavily involved in the regulation of cell apoptosis, survival, and regeneration is the Hippo pathway [ 11 ]. The core components of the Hippo pathway in mammals include kinases—mammalian sterile 20-like kinase 1/2 (MST1/2) and large tumor suppressor 1/2 (LATS1/2), adaptor molecules (salvador (SAV1) and MOB kinase activator 1 (MOB1)), the transcriptional co-activators Yes-associated protein (YAP), and WW domain containing transcription regulator 1 (WWTR1/TAZ) [ 8 , 11 ]. Activation of the Hippo pathway by phosphorylation of the kinases results in YAP inactivation and hence reduces the expression of its target genes, which include anti-apoptotic and pro-survival genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the genes that we identified to be differentially expressed in NOD and B6 ES cells, many were known to be involved in innate and adaptive immune responses. While some cytokines promote a tolerogenic environment, such as TGF-b or IL-10, others are known to support a diabetogenic environment, such as TNF and IL-6 [47]. Thus, we investigated whether NOD and B6 ES cells are already capable of responding to certain triggers of the innate immune system, and consequently might secret cytokines.…”
Section: Discussionmentioning
confidence: 99%